Antitumor Activity of Doxorubicin Encapsulated in Poly (ethylene glycol)-Coated Liposomes - MARUYAMA, Kazuo; UNEZAKI, Sakae; IWATSURU, Motoharu; HOSODA, Junichi; TSUCHIYA, Seishi (Biological & pharmaceutical bulletin, 1995)
The antitumor activity of doxorubicin (DXR) which had been encapsulated in poly (ethylene glycol) (PEG)-coated long-circulating liposomes was examined in mice inoculated with colon 26 carcinoma cells. Six mol% of the distearoylphosphatidylethanolamine derivative of PEGs with different molecular weights was incorporated in liposomes (90-110nm, mean diameter) composed of distearoylphosphatidylcholine/cholesterol (1/1, molar ratio), and the encapsulating efficiency of DXR in liposomes was more than 98% by the pH gradient method. Each concentration of DXR in blood and tumor tissue was significantly greater after administration of the drug encapsulated in PEG-coated liposomes (DXR-PEG-liposome) compared to the non-coated control liposomes or non-encapsulated free drug. DXR-PEG-liposome prepared with PEG1000 (DXR-PEG1000-liposome) more effectively increased the level of DXR in blood and tumor than did the preparations with PEG5000 or PEG12000. A single treatment with DXR-PEG1000-liposome (10mg DXR/kg) resulted in increased survival time. Further therapeutic improvement in terms of tumor growth retardation and prolongation of survival time were observed following multiple treatments with DXR-PEG1000-liposome (3×5mg DXR/kg). Long-circulating liposome coating optimized PEGs should be useful for the delivery of chemotherapeutic agents for the treatment of solid tumors.